THE ROLE OF GAT-TECHNOLOGIES IN THE ASSESSMENT OF SOILS OF DRY LANDS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article presents the state of dry gray and brown soils, common in the mountainous region, and their assessment based on digital technologies. Also, economic efficiency indicators were studied in the assessment and mapping of soil fertility based on GAT technologies.